2017
DOI: 10.1002/jbm.a.35981
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the anti‐inflammatory effects of phosphatidylserine‐containing liposomes by PEGylation

Abstract: Inhibiting liposome uptake by macrophages using polyethylene glycol (PEG) surface modifications is a widely used approach for extending the half-life of liposomes circulating in the blood. However, the biological effects of PEGylated liposomes on macrophages have not yet been thoroughly investigated. The purpose of this study was to examine the effects of PEGylated phosphatidylserine-containing liposomes (PEG-PSLs) on the expression of two inflammation-associated cytokines, tumor necrosis factor-α (TNF-α) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
2
7
1
Order By: Relevance
“…In accordance with previous literature, PEG concentration had a profound effect on liposome characteristics 34–37 . PEGylated liposomes with superior properties were achieved by through optimal PEG concentration.…”
Section: Resultssupporting
confidence: 89%
“…In accordance with previous literature, PEG concentration had a profound effect on liposome characteristics 34–37 . PEGylated liposomes with superior properties were achieved by through optimal PEG concentration.…”
Section: Resultssupporting
confidence: 89%
“…production such as Interleukin 6 (IL6) and Prostaglandin E2 (PGE2), in Interleukin 1 beta (IL-1β) stimulated in vitro and in vivo animal models [29], through induction of active anti-inflammatory or suppressive properties in macrophages [30]. Indeed, a previous study has shown the effects of PEGylated PS-containing liposomes on the expression of two inflammation associated cytoki nes, tumour necrosis factor-α (TNF-α) and transforming growth factor-β (TGF-β), in the murine macrophage-like cell line RAW 264.7 [31]. These results demonstrated that the incorporation of PEGylated PS-containing liposomes into cells decreased compared with non-PEGylated PS liposomes, suggesting that the interactions between PS and the PS receptors that influence TNF-α and TGF-β levels were differentially affected by the PEGylation of PS liposomes [31,32].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Indeed, a previous study has shown the effects of PEGylated PS-containing liposomes on the expression of two inflammation associated cytoki nes, tumour necrosis factor-α (TNF-α) and transforming growth factor-β (TGF-β), in the murine macrophage-like cell line RAW 264.7 [31]. These results demonstrated that the incorporation of PEGylated PS-containing liposomes into cells decreased compared with non-PEGylated PS liposomes, suggesting that the interactions between PS and the PS receptors that influence TNF-α and TGF-β levels were differentially affected by the PEGylation of PS liposomes [31,32]. As PEGylated PS containing liposomes are capable of efficiently inhibiting the inflammatory cytokine TNF-α without upregulating TGF-β mRNA [33], they demonstrate promising anti-inflammatory effect.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The activation and phenotype of macrophages is likely affected by implanted biomaterials, and the resulting state of macrophages may, in turn, determine the quality of tissue regeneration on the surface of the biomaterials. Since the beginning of biomaterial design, there have been many attempts to regulate the state of macrophages to improve their biocompatibility [5][6][7]. To enhance the biocompatibility of biomaterials, M2 polarization of macrophages is generally recommended, because anti-inflammatory M2 macrophages are supposed to end inflammation and promote tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%